Educational Environment, Ethnocentrism, and Prejudice Towards Indonesian Chinese - Baidi Bukhori (ANIMA Indonesian Psychological Journal, 2017)
Inter-ethnic prejudice is one of the problems faced by multi ethnic nations, including Indonesia. It does not only bring positive impacts in social interactions, but can also lead to social conflicts. To prevent the conflicts, an understanding of prejudice is required. So, the purposes of this study were: (1) To examine the effect of different educational environment on prejudice towards Chinese ethnic groups by controlling ethnocentrism; (2) To examine the influence of ethnocentrism on prejudice towards Chinese ethnic groups by controlling educational environments. Population in this study (N = 200) was non-Chinese students in Semarang. Sampling was done by applying a stratified sampling technique. Data were collected using the scales for both prejudice towards Chinese ethnic groups and ethnocentrism. Then, a statistical method using covariance analysis was used to analyze the data. Results revealed a difference in prejudice towards Chinese ethnic groups between students who studied at a college having Chinese students and those at a college having no Chinese students by controlling ethnocentrism. Besides, there was a significant ethnocentric role in prejudice towards Chinese ethnic groups by controlling educational environments.